2015
DOI: 10.1007/s11325-015-1189-8
|View full text |Cite
|
Sign up to set email alerts
|

Nasal nitric oxide in sleep-disordered breathing in children

Abstract: Compared to healthy controls, nNO is increased in children with SDB, but it is not correlated with disease severity. This is probably due to the local mechanical processes and snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Even the association of the eNO with the apnea-hypopnea index (AHI) is controversial. Indeed, while some studies found a strong and positive correlation between FeNO and AHI, with a r of 0.8–0.9 [23,33], or oNO and AHI ( r : 0.46) [32] and a negative one between CaNO and AHI, with a r of 0.9 [23], this was not confirmed by other studies [20,21,22,27,28,39,41].…”
Section: Resultsmentioning
confidence: 87%
“…Even the association of the eNO with the apnea-hypopnea index (AHI) is controversial. Indeed, while some studies found a strong and positive correlation between FeNO and AHI, with a r of 0.8–0.9 [23,33], or oNO and AHI ( r : 0.46) [32] and a negative one between CaNO and AHI, with a r of 0.9 [23], this was not confirmed by other studies [20,21,22,27,28,39,41].…”
Section: Resultsmentioning
confidence: 87%
“…In contrast, Petrosyan et al 85 found increased levels of FENO and exhaled carbon monoxide in patients with OSA; FENO decreased after 1 month of CPAP treatment. Recently, in a study by Gut et al, 94 nasal NO was higher in OSA and primary snoring compared with controls, and did not correlate with disease severity.…”
Section: Search For Other Techniques and Optional Biomarkersmentioning
confidence: 88%
“…Compared to the healthy controls, nNO is also increased in children with sleep-disordered breathing, but it is not correlated with disease severity. This is probably due to the local mechanical processes and snoring (45).…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%